Synthesis, structure, DFT study and molecular docking inspection of spirobi[hexahydropyrimidine]-diones derivative - Malahat Kurbanova; Suraj N. Mali; Fidan Gurbanova; Haya Yasin; Shailesh S. Gurav; Chin-Hung Lai (Chemical Physics Impact)
It has been established that three-component condensation of benzaldehyde, acetone and urea catalyzed H2SO4 leads to the formation of spirobi[hexahidropyrimidine]-dione derivatives. The structure of the synthesized compound has been proved by X-ray method. The results of the quantum theory of atom-in-molecule and noncovalent interaction index analysis showed no intramolecular hydrogen bonds in the molecule studied. However, it contains four NH bonds and two CO groups. Based on the result of the DFT-NBO analysis, it was the lone pairs of oxygen on the CO group which are forming strong orbital interactions with the antibonding orbital of the CN single bond. The molecular docking was performed to investigate potential binding interactions of the compound with four target proteins including 5I4T (HIV-1), 5R7Z, 6M71 and 6VYB (SARS-Cov-2). Additionally, in-silico drug-likeness and ADME studies suggested oral activity (violations ≤ 1) of scaffold and predicted to be actively effluxed by P-gp (PGP+).